2012
DOI: 10.1007/8904_2011_117
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Profile of the MUT Gene in Chinese Methylmalonic Aciduria Patients

Abstract: The mut-type methylmalonic aciduria (MMA, MIM 251000) is caused by a deficiency of mitochondrial methylmalonyl-CoA mutase (MCM, E.C. 5.4.99.2) activity, which results from defects in the MUT gene. To elucidate the mutation spectrum of the MUT gene in Chinese MMA patients, 13 exons of the MUT gene, including untranslated regions, were analyzed by PCR-based sequencing for 42 unrelated Chinese MMA patients. All the 42 patients were found to have at least one MUT mutation. A total of 41 mutations were identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Thus, the common genotypes appear to vary geographically around the world. The allele frequency of c.729_730insTT has been reported in two groups of Chinese patients (15.4% and 10.7%), compared with the 14.2% in our cohort, indicating a similar frequency among different groups of Chinese patients. However, c.729_730insTT was identified in 4 alleles in 151 European patients (1.3%), which was far lower than that in the Chinese population.…”
Section: Discussionsupporting
confidence: 72%
“…Thus, the common genotypes appear to vary geographically around the world. The allele frequency of c.729_730insTT has been reported in two groups of Chinese patients (15.4% and 10.7%), compared with the 14.2% in our cohort, indicating a similar frequency among different groups of Chinese patients. However, c.729_730insTT was identified in 4 alleles in 151 European patients (1.3%), which was far lower than that in the Chinese population.…”
Section: Discussionsupporting
confidence: 72%
“…The genotypes of Taiwanese patients appear to differ from the People’s Republic of China, where the most common defect (12 out of 78 mutant alleles, 15%) is c.729_730insTT (p.D244Lfs*39) [24], which only occurred once out of 56 mutants alleles (1.8%) from our data in Taiwan. On the contrary, the genotypes in Taiwan appear similar to Southern part of China, where the leading mutant allele is G427D, followed by c.1630_1631GG > TA (p.G544X) [25] Our findings also differ from those of Japan, where the most frequent mutations are p.E117X, c.385 + 5G > A, p.R369H, p.L494X, and p.R727X [26]. We also found that 17 (81%) patients were classified as mut 0 .…”
Section: Discussionmentioning
confidence: 99%
“…The patients were diagnosed biochemically and genetically (patient 1, genetic analysis was not available; patient 2, c.323G>A (p.R108H)/ c.729_730insTT; patient 3, c.1560+1 G>T/c.2075 T>C (p.L692P); patient 4, c.683G>A (p.R228Q)/c.1106G>A (p.R369H)). Several of these mutations have been reported previously as pathogenic mutations [15][16][17][18].…”
Section: Patients and Healthy Individualsmentioning
confidence: 95%